Discrepancies between JWST Observations and Simulations of Quenched Massive Galaxies at z > 3: A Comparative Study with IllustrisTNG and ASTRID - Emma Jane Weller; Fabio Pacucci; Yueying Ni; Lars Hernquist; Minjung Park (The Astrophysical Journal)
Recent JWST observations have uncovered an unexpectedly large population of massive quiescent galaxies at z > 3. Using the cosmological simulations IllustrisTNG and ASTRID , we identify analogous galaxies and investigate their abundance, formation, quenching mechanisms, and post-quenching evolution for stellar masses $9.5\lt {log}_{10}(M_{\star }/M_{{\odot }})\lt 12$ . We apply three different quenching definitions and find that both simulations significantly underestimate the comoving number density of quenched massive galaxies at z ≳ 3 compared to JWST observations by up to ∼2 dex. In both simulations, the high- z quenched massive galaxies often host overmassive central black holes above the local M _BH – M _⋆ relation, implying that AGN feedback is key in quenching galaxies in the early Universe. The typical quenching timescales for these galaxies are ∼200–600 Myr. IllustrisTNG primarily employs AGN kinetic feedback, while ASTRID relies on AGN thermal feedback at z > 2.3, which is less effective and has a longer quenching timescale. Although these simulations differ in many aspects, making a direct comparison challenging, our findings suggest the need for improved physical models of AGN feedback in galaxy formation simulations. At lower stellar masses, the quenched galaxies have denser local environments than the star-forming galaxies, suggesting that environmental quenching helps quench less-massive galaxies. We also study the post-quenching evolution of the high- z massive quiescent galaxies and find that many experience subsequent reactivation of star formation, evolving into primary progenitors of z = 0 brightest cluster galaxies.